2017
DOI: 10.1007/s00394-017-1424-0
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of oral vitamin B12 is influenced by B12 status and B12 form: an experimental study in rats

Abstract: PurposeHydroxocobalamin (HOCbl) is the dominating Cbl form in food, whereas cyanocobalamin (CNCbl) is common in vitamin pills and oral supplements. This study compares single-dose absorption and distribution of oral HO[57Co]Cbl and CN[57Co]Cbl in Cbl-deficient and normal rats.MethodsMale Wistar rats (7 weeks) were fed a 14-day diet with (n = 15) or without (n = 15) Cbl. We compared the uptakes of HO[57Co]Cbl (free or bound to bovine transcobalamin) and free CN[57Co]Cbl administered by gastric gavage (n = 5 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 22 publications
16
28
0
Order By: Relevance
“…The rational is that this form of the vitamin is both chemically stable and cheap. In agreement with the previous studies [11][12][13][14], we find that CN-B12 induces a higher increase in the circulating total Cbl in comparison to HO-B12. Interestingly, administration of HO-B12 is as efficient-if not slightly better-in improving other markers of an impaired B12 status, notably MMA.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The rational is that this form of the vitamin is both chemically stable and cheap. In agreement with the previous studies [11][12][13][14], we find that CN-B12 induces a higher increase in the circulating total Cbl in comparison to HO-B12. Interestingly, administration of HO-B12 is as efficient-if not slightly better-in improving other markers of an impaired B12 status, notably MMA.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, administration of HO-B12 is as efficient-if not slightly better-in improving other markers of an impaired B12 status, notably MMA. This result is in accord with our previous studies in rats [12,13]. Thus, based on our present data, we conclude that the increase in serum Cbl upon administration of CN-B12 does not mirror a superior effect of this vitamin form, but rather shows that CN-B12 has a tendency to fall behind HO-B12 in the rates of tissue uptake.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here, ADO-B 12 acts as a cofactor for methylmalonyl-CoA mutase in the conversion of methylmalonyl-CoA to succinyl-CoA in the mitochondria. CH 3 -B 12 acts as a cofactor for methionine synthase in the folatedependent methylation of homocysteine to methionine in the cytoplasm (1,2) .Both human and animal studies have demonstrated that synthetic and natural forms of B 12 are absorbed equally (7)(8)(9)(10)(11) . However, our recent data show that HO-B 12 accumulates in the liver to a higher degree than CN-B 12 , but that the patterns are opposite in the brain and plasma.…”
mentioning
confidence: 99%